L’esilio volontario di Carlo Goldoni a Parigi - Török, Tamara (Verbum – Analecta Neolatina, 2008)
At the peak of his career and after some unbearable literary conflicts, Carlo Goldoni accepts the invitation of the Théâtre Italien (’Italian Theatre’) in Paris and leaves Venice. Una delle ultime sere del Carnovale (’One of the Last Nights of the Carnival’) is the comedy with which he says goodbye to his Venice audience, and in the form of an allegory, entering the comedy behind its protagonist, Anzoletto, he speaks about his professional reasons to leave Venice. This parallelism between Anzoletto and Goldoni is analyzed through the latest theatrical version of this comedy that was staged at the Katona Theatre in Budapest.